Breast and bowel cancer screening uptake patterns over 15 years for UK south Asian ethnic minority populations, corrected for differences in socio-demographic characteristics - Price Charlotte; Szczepura Ala; Gumber Anil (BMC, 2008)
Abstract Background A number of studies have reported low uptake of cancer screening programmes by South Asian populations in the UK. However, studies to date have not adjusted findings for differences in demographics and socio-economic status of these populations. Methods Subjects: All residents in Coventry and Warwickshire, UK, eligible for screening. Uptakes compared for round 1 (2000-02) and round 2 (2003-05) of a national bowel cancer screening pilot, and for rounds 1, 2 and 5 of the established NHS breast cancer screening programme (commenced 1989). Data: Bowel screening data were analysed for 123,367 invitees in round 1 and 116,773 in round 2 (total 240,140 cases). Breast screening data were analysed for 61,934, 62,829 and 86,749 invitees in rounds 1, 2 and 5 respectively (total 211,512 cases). Analysis: Screening uptake was compared for two broad meta-categories (South Asian and non-Asian) and for five Asian subgroups (Hindu-Gujarati; Hindu-Other; Muslim; Sikh; South Asian Other). Univariate and multivariate analyses examined screening uptake and various demographic attributes of invitees, including age, gender, deprivation and ethnic group. Results South Asians demonstrated significantly lower (p < 0.001) unadjusted bowel screening uptake; 32.8% vs. 61.3% for non-Asians (round 1). Rates were particularly low for the Muslim subgroup: 26.1% (round 1), 21.5% (round 2). For breast screening, a smaller difference was observed between South Asians and non-Asians; initially 60.8% vs. 75.4% (round 1) and later 66.8% vs. 77.7% (round 5). Thus, the disparity reduced gradually over time, alongside an overall trend of increased uptake. However, figures remained consistently low for Muslims (51% in rounds 1 and 5). After adjusting for age, deprivation (and gender), bowel screening uptake remained significantly lower for all South Asian subgroups. After similar adjustments, breast screening uptake remained lower for all subgroups except Hindu-Gujaratis. For Muslims registered with an Asian (vs. non-Asian) GP, bowel screening uptake was significantly lower (p < 0.001). However, breast screening uptake for Muslims with an Asian (vs. non-Asian) GP showed no difference (p = 0.12) in the same period. Colonoscopy and breast assessment uptakes were similar for both meta-categories, but Asian response time appeared slower for colonoscopy. The percentage of abnormal FOBT results was significantly higher for South Asian invitees. A slight increase in abnormal mammograms was observed for Muslims over time (2.7% to 4.2% in rounds 1 and 5 respectively). Conclusion The lower cancer screening uptakes observed for the South Asian population cannot be attributed to socio-economic, age or gender population differences. Although breast screening disparities have reduced over time, significant differences remain. We conclude that both programmes need to implement and assess interventions to reduce such differences.